DAYA TERIMA DAN KADAR PROTEIN SERTA VITAMIN A OTAK-OTAK IKAN KEMBUNG DENGAN PENAMBAHAN TEPUNG TEMPE DAN WORTEL - Nadimin Nadimin; Zakaria Zakaria; Rifka Annisa (Jurusan Gizi Poltekkes Kemenkes Makassar, 2021)
Otak-otak are foods made from Spanish mackerels that are quite expensive. Chub mackerels can replace Spanish mackerel because it has an economical price and contains high protein nutrients. The addition of tempeh flour and carrots to the chub mackerel fish otak-otaks is expected to be able to meet the nutritional needs of toddlers stunting. This research aims to determine acceptance and assess levels of protein and vitamin A otak-otaks of chub mackerel with the addition of tempeh flour and carrots. This type of research is laboratory research with post test group design. The spanish mackerel otak-otaks that are sold in the market are compared to the chub mackerel otak-otaks without addition and the chub mackerel otak-otaks with the addition of tempeh flour and carrots. Acceptability was assessed based on the hedonic test results of 30 panelists, then analyzed the levels of protein and vitamin A. The results of the data were analyzed using Kruskal Wallis and Mann Whitney Test. The results showed that the acceptance of the otak-otaks for the aspects of color, aroma, texture and taste was the best, namely the otak-otaks of spanish mackerel which were sold in the market, then the otak-otaks of chub mackerel with the addition of tempeh flour and carrots and the lowest was the otak-otak chub mackerel without addition. The protein content of spanish mackerel fish ota-otaks sold in the market is 14.630%, chub mackerel otak-otaks is 11.083% and chub mackerel fish otak-otaks with the addition of tempeh and carrot flour is 12.573%. The levels of vitamin A spanish mackerel fish otak-otaks sold in the market are 28.65 ppm, chub mackerel otak-otaks are 30.47 ppm and chub mackerel fish otak-otaks with the addition of tempeh and carrot flour is 39.18 ppm.Keywords : Protein, vitamin A, carrots, chub mackerel, otak-otaks, tempeh flour